The ancient critic at work: Terms and concepts of literary criticism in Greek scholia (Cambridge University, 2013)
The large but underrated corpus of Greek scholia, the marginal and interlinear notes found in manuscripts, is a very important source for ancient literary criticism. The evidence of the scholia significantly adds to and enhances the picture that can be gained from studying the relevant treatises (such as Aristotle's Poetics): scholia also contain concepts that are not found in the treatises, and they are indicative of how the concepts are actually put to use in the progressive interpretation of texts. The book also demonstrates that it is vital to study both ancient terminology and the cases where a particular phenomenon is simply paraphrased. Nineteen thematic chapters provide a repertoire of the various terms and concepts of ancient literary criticism. The relevant witnesses are extensively quoted in Greek and English translation. A glossary of Greek terms (with translation) and several indices enable the book also to be used for reference.